Conception of Social Management and Deliberative Citizenship in the Assessment of Social Control of the Municipal Council of Education of Grajaú – MA (Research, Society and Development, 2021)
Municipal Councils of Education represent an important instrument in social management. In this context, this paper aims to evaluate social management and deliberative citizenship in the evaluation of social control of the Municipal Education Council of the city of Grajaú-MA. Initially, a bibliographic search was performed based on authors who studied the theme in question. There was a non-participant observation of WEC activities. Subsequently, the questionnaires were selected, the results were shown in radar graphs, as well as a presentation of the interviews alongside the full members and alternate members of the different filters that make up the consulted council. Given the exposure, the results achieved reflect a still poor participation, or compromise the effectiveness of deliberative citizenship.